Development levels for time planning model ofroad constru ction at design stages - T. V. Bobrova; E. A. Pokalyukhina (Вестник СибАДИ, 2024)
Introduction. The experience of Russian computer companies in the field of information modelling technologies (IMT) in construction is analyzed. The attention to the role of standardization and classification of construction information (CSI) for coding elements of the digital information model (DIM) at the stages of organizational design and calendar planning is drawn. The specificity of linear objects with respect to the level of elaboration of model elements and their attribute characteristics at different planning levels is noted. Models and methods. The necessity of an individual approach to the decomposition of road structure elements taking into account the complex of natural and man-made factors is substantiated. At different stages of designing the organization of road construction, the timetable with different degrees of detail depending on the design objectives and available information about the object is presented. The parameters of specialized flows of a linear object, limitations and criteria for the optimality of the calendar plan at the design stage of the construction organization (CO) are determined. The level of elaboration of the model elements at the stage of work production by the contracting organization has been increased. The developed algorithm for forming a complex flow graph in the form of a flowchart and a DIM is presented.Results. The use of the method is considered on the examples of structuring the elements of the object and technological processes at the stage of work production by the contracting organization, taking into account different options and schemes for organizing the work of specialized streams. The design results are presented in the form of a calculation matrix, a cyclogram and a Gantt graph in the MS Project program.Discussion and conclusion. The development of the basic information for the model of the calendar plan for the construction of a road at different stages of design in an integrated general data environment is presented. The use of linear road is justified.  zoning as a method of decomposition of a linear object at the stages of CAD, POS and work production by the contracting organization. The structural elements of the design at the final stage (work production by the contracting organization) are linear design and technological modules and specialized flows formed on the basis of maps of labor processes of the contracting organization.